2019
DOI: 10.1016/j.enpol.2019.110991
|View full text |Cite
|
Sign up to set email alerts
|

Do technical improvements lead to real efficiency gains? Disaggregating changes in transport energy intensity

Abstract: Fuel economy standards are a key measure to increase the rate of efficiency improvements in passenger cars. The fuel consumption of vehicles can be improved in three ways: incremental technical efficiency improvements within powertrain technologies, market shifts to more efficient types of powertrains and by limiting increases in the size and performance of vehicles. This study quantifies the effect of each of these three drivers on the fuel consumption of British vehicles between 2001 and 2018 using driver-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…The real-world fuel efficiency of vehicles from model years 2001-2018 is sourced from past work by the authors (Craglia and Cullen, 2019). These are linearly extrapolated backwards to 1994 in order to attain the fuel efficiency of all vehicles in use in the base year 2018.…”
Section: Modelling the Efficiency Of New Vehiclesmentioning
confidence: 99%
“…The real-world fuel efficiency of vehicles from model years 2001-2018 is sourced from past work by the authors (Craglia and Cullen, 2019). These are linearly extrapolated backwards to 1994 in order to attain the fuel efficiency of all vehicles in use in the base year 2018.…”
Section: Modelling the Efficiency Of New Vehiclesmentioning
confidence: 99%
“…Using bottom‐up data, the magnitude of steel flows into and out of the UK vehicle stock were estimated for each year given that the following quantities were known: the number of new and scrapped vehicles (UK Department for Transport, 2019a, 2019c, 2019b), the average mass of new vehicles (Craglia & Cullen, 2019; McGregor, 2017) and the average steel content of new vehicles (Serrenho, Norman, & Allwood, 2017). In general, estimates of the steel scrap output from the vehicle stock is not publicly available and requires creating a stock model to estimate the age distribution of vehicles on the road.…”
Section: Methodsmentioning
confidence: 99%
“…A previous paper by the authors [40] built a dataset of vehicles sold between 2001 and 2018 using a combination of publicly available data sources [41][42][43]. Using this data, we attribute a size segment (e.g.…”
Section: Datamentioning
confidence: 99%
“…The dataset created in [40] sourced driver reported, realworld fuel consumption records for new British vehicles sold between 2001 and 2018 and was able to determine a sales-weighted estimate of new car, real-world fuel consumption for the first time. This showed that the difference between manufacturer reported (type-approval) fuel consumption and driver reported (real-world) fuel consumption has been increasing over time.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation